Does coating resistance control corrosion? - Sykes, John (Elsevier, 2017)
Bacon, Smith and Rugg first identified a link between the DC resistance of a coated panel after exposure to salt solution and the performance of the coating in an exposure test. Mayne explained this as “resistance inhibition”. This paper will consider what coating resistance measured by Electrochemical Impedance Spectroscopy (EIS) tells us about factors controlling the corrosion process. It shows that the activation energy for ion conduction does not correspond with that for the corrosion process, suggesting that the paint resistance we measure is not the controlling factor. Furthermore, tests on a model galvanic cell reveal a significant influence of both electrode polarisation and resistance inhibition.